E-013 Coil herniation and retinal/vitreous hemorrhage in a patient with antiphospholipid antibody syndrome undergoing balloon assisted coil embolization of unruptured ICA aneurysm. (4th July 2012) - Gupta, V; Gandhi, C; Prestigiacomo, C; Bhagat, N; Turbin, R; Gupta, G
Abstract : Antiphospholipid antibody syndrome (APS) is a well-recognized cause of hyper coagulation causing arterial/venous thrombosis and/or pregnancy morbidity. Thromboembolic complications remain the main concern during endovascular coil embolization of aneurysms. Retinal and vitreous hemorrhages in association with this syndrome as a post coiling complication of unruptured intracranial aneurysm has not been previously reported. We report the case of a 48-year-old woman with underlying APS who underwent balloon assisted coil embolization of an unruptured right ICA aneurysm. There was herniation of the second coil requiring coil retrieval with subsequent non flow limiting herniation of the first coil left in situ on anticoagulation. In the immediate post procedure period, she developed preretinal, intraretinal and vitreous hemorrhages requiring temporary withholding anticoagulation therapy with careful resumption. Retinal/vitreous hemorrhages in a patient with APS presents a complex management challenge in the context of a herniated coil loop during endovascular aneurysm therapy. Competing interests: None.